Studies of microclimatic conditions in summer moong as influenced by different mulches - KUMAR, VINOD; BISHNOI, O. P.; SINGH, SURENDER; RAO, V. U. M. (MAUSAM, 1995)
A field experiment was conducted during summer season of 1990 at research farm of Department of Agricultural Meteorology, Haryana Agricultural University, Hisar to study the microclimatic conditions in moong with the use of mulches. Latent heat enelgY and sensible heat energy were the main components of net energy. Among the various treatments, the latent heat energy use was found higher in black polythene sheet mulch. Soil temperature values were low in straw and white polythene mulch than black polythene mulch treatment